2004
DOI: 10.1038/sj.jea.7500389
|View full text |Cite
|
Sign up to set email alerts
|

A sensitivity analysis of bias in relative risk estimates due to disinfection by-product exposure misclassification

Abstract: We conducted a sensitivity analysis of relative risk estimates using local area mean disinfection by-product exposures. We used Monte Carlo simulations to generate data representing 100 towns, each with 100 births (n ¼ 10,000). Each town was assigned a mean total trihalomethane (TTHM) exposure value (mean ¼ 45, SD ¼ 28) based on a variable number of sampling locations (range 2-10). True maternal TTHM exposure was randomly assigned from a lognormal distribution using that town's true mean value. We compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Although colorectal cancer risk has been linked with a variety of ecological based water studies [27-29], with the exception of rodent studies, we found no strong previous evidence in the literature suggesting and/or supporting a specific association of rectal cancer risk with exposure to bromoform in humans. Studies of risk associated with exposure to DBPs are often based on indirect exposure assessments that rely on relatively large scales of geographic classifications of DBPs [54], and classification of exposed and unexposed groups is often made based on town, parish, or areas served by specific water treatment systems [28,29,31,42,55]. …”
Section: Discussionmentioning
confidence: 99%
“…Although colorectal cancer risk has been linked with a variety of ecological based water studies [27-29], with the exception of rodent studies, we found no strong previous evidence in the literature suggesting and/or supporting a specific association of rectal cancer risk with exposure to bromoform in humans. Studies of risk associated with exposure to DBPs are often based on indirect exposure assessments that rely on relatively large scales of geographic classifications of DBPs [54], and classification of exposed and unexposed groups is often made based on town, parish, or areas served by specific water treatment systems [28,29,31,42,55]. …”
Section: Discussionmentioning
confidence: 99%
“…This method may be appropriate for adjustment of biased exposure estimates when systems with high spatial variability must be utilised; however, as recently reported in a paper by Wright and Bateson, the applicability of this method may depend on degree of spatial variability and magnitude of ''true'' risk estimated for a given birth outcome. 4 We evaluated two methods for selection of populations served by water distribution systems with minimal spatial variability in the concentrations of TTHMs. Using the two way ANOVA method, we compared TTHM levels between four sampling points in the distribution system controlling Table 2 Total and individual THMs and sum of 5 HAAs (mg/l) for plants categorised into each of three profiles by the ANOVA and cut-points methods for the influence of season and identified 17 sites with low spatial variability in four consecutive seasons.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, there is general agreement that limitations in exposure assessment have resulted in substantial misclassification of exposure in these studies, making the true risk difficult to determine. [1][2][3][4] For example, in most epidemiological studies conducted to date, all persons living within the boundaries of a water distribution system have been assigned a common exposure value based on facility-wide averages of trihalomethane (THM) concentrations for a point in time of interest. Use of public water facility monitoring data can result in exposure misclassification when persons living at different locations within a distribution system are exposed to significantly different concentrations of THMs but are assigned a common exposure level.…”
mentioning
confidence: 99%
“…Studies of pregnant women are particularly susceptible because the lifealtering event of pregnancy might cause direct changes in selfawareness and intentional changes in behavior over a relatively short-time period. Previous research has suggested that exposure to disinfection by-products (DBPs) in public tap water may be associated with adverse pregnancy outcomes (Nieuwenhuijsen et al, 2000;Graves et al, 2001;Bove et al, 2002), but many of the existing studies have relied solely on concentration of DBPs in municipal water sources, potentially resulting in exposure misclassification by ignoring variation in behaviors (Waller et al, 2001;Wright and Bateson 2005;Wright et al, 2006). Recent improvements in exposure assessment have resulted in collection and integration of information about individual women's water use habits .…”
Section: Introductionmentioning
confidence: 99%